2018
DOI: 10.1093/jscr/rjy003
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of massive lower gastrointestinal bleeding from a ruptured splenic artery aneurysm

Abstract: Splenic artery aneurysms (SAAs) are an extremely rare cause of asymptomatic massive lower gastrointestinal bleeding with less than a handful of patients surviving such a presentation. A 24-year-old female presented in shock after multiple episodes of massive rectal bleeding. Imaging revealed a heterogeneous mass arising from the tail of the pancreas eroding into the splenic flexure of the colon. Further episodes of bleeding led to an exploratory laparotomy. Intraoperatively, a suspected neoplastic process aris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Resection of adjacent structures is done based on invasion. Of note, in our case we were able to preserve the stomach in comparison to the case described by Maharaj et al [1]. This was possible because of CT diagnosis of SAA and intraoperative confirmation of the same where there was no invasion into the stomach and no need to remove the sac since it was not a tumor.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Resection of adjacent structures is done based on invasion. Of note, in our case we were able to preserve the stomach in comparison to the case described by Maharaj et al [1]. This was possible because of CT diagnosis of SAA and intraoperative confirmation of the same where there was no invasion into the stomach and no need to remove the sac since it was not a tumor.…”
Section: Discussionmentioning
confidence: 51%
“…There are reported cases of erosion and rupture into adjacent organs such as the stomach (presenting with symptoms of an upper gastrointestinal bleed), the duodenum (melena and hematemesis), as well as erosion into the splenic vein (resulting in an arteriovenous fistula with mesenteric steal and ischemic small bowel) [7]. As with the case outlined above, there have been cases where an SAA has eroded into the colon and resulted in hematochezia with hypovolemic shock [1], [8]; less than 200 such cases are described in the literature [9].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the common case, the rupture of spleen arrhythmia is more likely to happen when it is bigger than 2 centimeters or in a person who is pregnant, and care should be taken to treat these individuals (11). At present, the favored technique of treatment is embolization; moreover, embolization might fail in cases presenting tortuous splenic arteries, and there is no little follow-up information for this method, and recurrence is a possible long-term hazard.…”
Section: Discussionmentioning
confidence: 99%
“…Arteriointestinal fistula can also occur rarely in patients with no history of surgery. A previous study reported a case without previous operation in which a splenic artery aneurysm ruptured into the splenic flexure of the colon, leading to massive lower gastrointestinal bleeding [13]. The clinical manifestations of arteriointestinal fistula are diverse and non-specific.…”
Section: Discussionmentioning
confidence: 99%